ANALISIS PENGARUH EXPERIENTIAL MARKETING DAN HARGA TERHADAP CUSTOMER LOYALTY SMARTPHONE BERSISTEM OPERASI ANDROID DI KOTA BENGKULU - Meiffa Herfianti; Rika Dwi Yulihartika (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2020)
The purpose of this study was to investigate the effect of experiential marketing and price on customer loyalty through customer satisfaction as intermediate variable. Explanatory research was conducted by using questionnaires. The quistionnaires were distributed to the 250 respondent who had utilized smartphone OS Android more than 1 years. In the data analisys, the researcher used Structural Equation Model (SEM) with AMOS. The results show that the models were appropriate with the Goodness and Index Criteria Chisquare total = 469.122; and significance probability = 0,000; RMSEA = 0,071; CMN/DF = 1,938; TLI = 0,957; CFI = 0,896; GFI = 0,893 and AGFI = 0,947. According to the results, it can be concluded that the model was accepted. There are some implication from this study. Android. Inc., must create a point of differentiation to better involve consumers. Another implications is using WOM (word of Mouth), because that strategy are very useful to targetting adolescent consumers. Otherwise, Android. Inc,. should hold more events and sponsorship in order to close to their consumers.Â Keywords: Experiential Marketing, Price Customer Satisfaction And Customer Loyalty